TRAIL receptor agonist conatumumab with modified FOLFOX6 plus bevacizumab for first‐line treatment of metastatic colorectal cancer: A randomized phase 1b/2 trial. Issue 24 (1st October 2013) - Fuchs, Charles S.; Fakih, Marwan; Schwartzberg, Lee; Cohn, Allen L.; Yee, Lorrin; Dreisbach, Luke; Kozloff, Mark F.; Hei, Yong‐jiang; Galimi, Francesco; Pan, Yang; Haddad, Vincent; Hsu, Cheng‐Pang; et al.
Abstract : BACKGROUND: In patients with previously untreated metastatic colorectal cancer (mCRC), we conducted a phase 1b/randomized phase 2 trial to define the safety, tolerability, and efficacy of mFOLFOX6 plus bevacizumab (mFOLFOX6/bev) with conatumumab, an investigational, fully human monoclonal IgG1 antibody that specifically activates death receptor 5 (DR5). METHODS: Twelve patients were enrolled in a phase 1b open‐label dose‐escalation trial of conatumumab with mFOLFOX6/bev; thereafter, 190 patients were randomized 1:1:1 to receive mFOLFOX6/bev in combination with 2 mg/kg conatumumab, 10 mg/kg conatumumab, or placebo. Therapy cycles were repeated every 2 weeks until disease progression or the occurrence of unacceptable toxicity. RESULTS: In phase 1b, conatumumab with mFOLFOX6/bev was tolerated without apparent added toxicity over mFOLFOX6/bev alone. In phase 2, conatumumab with mFOLFOX6/bev did not confer a benefit in progression‐free survival when compared with placebo with mFOLFOX6/bev. Toxicity was similar in all treatment arms. Following treatment, similar increases in circulating caspase‐3 levels were observed in all arms. CONCLUSIONS: Conatumumab with mFOLFOX6/bev did not offer improved efficacy over the same chemotherapy with placebo in first‐line treatment of patients with mCRC. These data do not support further development of conatumumab in advanced CRC. Cancer 2013;119:4290–4298 . © 2013 American Cancer Society . Abstract : In this phase 1b/randomized phase 2 trial of conatumumab with mFOLFOX6/bevacizumab for first‐line treatment of metastatic colorectal cancer, conatumumab had a manageable toxicity profile but did not significantly improve progression‐free survival or overall survival compared with placebo. These data do not support further development of conatumumab in advanced colorectal cancer.